Delayed replantation of rat teeth after use of reconstituted powdered milk as a storage medium - Leticia Vendrame dos Santos, Claudia [UNESP]; Sonoda, Celso Koogi [UNESP]; Poi, Wilson Roberto [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Marcal Mazza Sundefeld, Maria Lucia [UNESP]; Negri, Marcia Regina (Wiley-Blackwell Publishing, Inc, 2009)
Minimal extraoral dry storage period and moist storage for the avulsed tooth are identified as key steps for the treatment protocol of tooth replantation. Among the possible moist storage media, bovine milk has stood out because of its capacity of preserving the integrity of the periodontal ligament (PDL) fibers. This condition has attracted the attention to investigate the use of powdered milk, which is one of the presentation forms of bovine milk, as a feasible storage medium in cases of delayed tooth replantation. The aim of this study was to evaluate the healing process after delayed replantation of rat teeth stored in reconstituted powdered milk and long shelf-life (ultra high temperature) whole milk. Forty maxillary right rat incisors were assigned to four groups (n = 10): group I - the teeth were extracted and immediately replanted into theirs sockets; group II - the teeth were stored for 60 min in 200 ml of freshly reconstituted powdered milk; group III - the teeth were stored for 60 min in 200 ml of long shelf-life whole milk; group IV - the teeth were kept dry for the same time. All procedures were performed at room temperature. Next, the root canals of teeth in groups II, III, and IV were instrumented, filled with a calcium hydroxide-based paste, and replanted into their sockets. All animals received systemic antibiotic therapy and were killed by anesthetic overdose 60 days after replantation. The pieces containing the replanted teeth were removed, fixed, decalcified, and paraffin-embedded. Semi-serial 6-mu m-thick sections were obtained and stained with hematoxylin and eosin for histomorphological analysis. There was statistically significant difference (P < 0.05) between groups I and IV regarding the presence of replacement resorption and PDL remnants on root surface. The powdered milk and long shelf-life whole milk presented similar results to each other and may be indicated as storage media for avulsed teeth.